Distributed control of virtual energy storage systems for voltage regulation in low voltage distribution networks subjects to varying time delays - Kang, Wenfa; Guan, Yajuan; Wang, Hongyi; Vasquez, Juan C.; Agundis-Tinajero, Gibran D.; Guerrero, Josep M. (Applied energy, 2024)
Distributed communication-based strategies are popular for regulating nodal voltages in distribution networks with high penetration of Photovoltaic (PV) sources. Time delays inevitably pose challenges to efficient voltage regulation and power sharing. In response, this paper presents a distributed, event-triggered voltage regulation approach that enables power sharing across virtual energy storage systems (VESS) with different parameters while accommodating diverse time delays. The process begins by determining the delay margin for the primary Volt/Watt controller in a low-voltage distribution network (LVDN), laying the foundation for stable feedback control gain design. To accommodate any arbitrary large and time-varying delays, a distributed resilient event-triggered secondary controller for VESS is designed to share voltage regulation tasks according to their capacities and state of energy (SoE) values. A mathematical analysis, grounded in the Lyapunov–Krasovskii approach, evaluates the stability and convergence of the proposed controller amidst time delays thoroughly. To validate the proposed method, simulation studies are conducted, which demonstrate the effectiveness in mitigating voltage limit violations, even with variable communication delays, and highlight balanced power sharing and SoE among VESS. •Single algorithm for voltage regulation, power sharing, and SoE balance with reduced communication requirements.•Investigates maximal time delay margin for primary Volt/Watt controller, ensuring stable voltage feedback control.•Introduces VESS controller for time-varying delays, efficiently sharing voltage regulation tasks among VESS using low-gain theory.